Characterization of Additively Manufactured Ti-6Al-4V with Process Parameter Induced Defects - Rutkowski, Kourtney (My University, 2019)
Additive manufacturing (AM) has the ability to revolutionize a multitude of industries, and while the technology has been around for a few decades, the additive manufacturing of metals is still a relatively new development in the field. The Defense industry has been using AM ever since it was invented in the 1980?s, and recently the Navy has taken interest in being able to use Additively Manufactured (AM) parts on their Naval air fleet. By using AM parts, the Navy can improve fleet readiness, increase the speed of maintenance with on demand part reproduction, and increase the speed of the fleet itself by reducing the overall weight of the aircrafts. Titanium alloys are lightweight with a high strength to weight ratio and have a good creep resistance at high temperatures. This makes it an ideal material to use in aerospace applications, such as in the engines. Direct Metal Laser Sintering (DMLS) is an innovative AM system that can create large components near to the final shape and can create small complex parts in their final shape. In this study, AM Ti-6Al-4V with intentionally induced defects created via DMLS will be tested using MicroTensile testing techniques. These defects are induced by varying the process parameters, and the purpose of this study is to analyze how changing these parameters affect the mechanical behavior and microstructure of the material. Other factors, such as position dependence will also be looked at.
Keywords: Additive Manufacturing; Defects; Microsample; Tensile Testing; Ti-6Al-4V